2018
DOI: 10.3892/ijo.2018.4263
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 43 SUMOylation improves gap junction functions between liver cancer stem cells and enhances their sensitivity to HSVtk/GCV

Abstract: Connexin 43 (Cx43) can be modified and regulated by small ubiquitin-like modifier (SUMO)1; however, its role in liver cancer stem cells is poorly understood. In this study, we found a significant difference in the expression of Cx43 and SUMO1 between cancer stem cells and non-cancer stem cells in liver cancer. In liver cancer stem cells, Cx43 was almost absent, although the level of SUMO1 was significantly higher than that in non-cancer stem cells. Further experiments confirmed that the conjugated site of Cx43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…A recent work has found that the expression levels of Cx43 and Cx46 were increased and reduced, respectively, during GSC differentiation and that targeting of Cx46 compromises GSC maintenance [56]. While Cx43 is almost absent in liver CSCs [57], the accumulation of cytoplasmic Cx32 has been associated with metastasis and enhanced self-renewal of CSCs in human HuH7 hepatoma cells [58]. Some subtypes of breast cancer cells positive for the putative CSC marker CD44 express Cx43 [59, 60].…”
Section: Complex Roles Of Connexins In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…A recent work has found that the expression levels of Cx43 and Cx46 were increased and reduced, respectively, during GSC differentiation and that targeting of Cx46 compromises GSC maintenance [56]. While Cx43 is almost absent in liver CSCs [57], the accumulation of cytoplasmic Cx32 has been associated with metastasis and enhanced self-renewal of CSCs in human HuH7 hepatoma cells [58]. Some subtypes of breast cancer cells positive for the putative CSC marker CD44 express Cx43 [59, 60].…”
Section: Complex Roles Of Connexins In Cancermentioning
confidence: 99%
“…refs. [114–117]), including a recent one in breast cancer [118] and liver cancer, in which the co-expression of Cx43 and SUMO1 in liver CSCs increased GJIC and their sensitivity to HSV-TK/GCV therapy in vitro and in vivo [57]. However, other studies reported no evidence for a GJIC-mediated bystander effect [119].…”
Section: Targeting Of Connexins In Cancer: Therapeutic Opportunities mentioning
confidence: 99%
“…A previous study indicated that Connexin 43 (Cx43), which is a protein involved in gap junctional intercellular communication, can be covalently modified and regulated by SUMO1 in liver cancer stem cells ( 57 ). In addition, Cx43 SUMOylation can improve gap junction functions and enhance cell sensitivity to HSVtk/GCV ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the level of CSCs, many studies have found that some properties of CSCs, such as self-renewal, depend on GJIC in breast and hepatic cancers [108,109]. In addition, it has been found that GIJC was an integral part of CSC function also resulting in tumor progression [110,111]. Hitomi and colleagues demonstrated that GJs are present in glioblastoma CSCs and that Cx46 is essential for CSC proliferation, self-renewal, and tumor initiation in vivo, whereas Cx43 is expressed by non-CSCs [110].…”
Section: Gjic and Hallmarks Of Cancermentioning
confidence: 99%